Development of deep-underground engineering structures via 2D and 3D RQD prediction using non-invasive CSAMT - Muhammad Hasan; Lijun Su; Peng Cui; Yanjun Shang (Scientific Reports)
Abstract The stability criterion based on the characterization of rock masses can be used to advance deep underground engineering projects. A key geomechanical criterion in geotechnical engineering is rock quality designation (RQD), which assesses risk for engineering design success criteria. Time, cost, and credibility constraints make it difficult to accurately estimate RQD. Point-scale data makes engineering design less precise and confusing, while traditional drilling for RQD estimation are expensive and time-consuming. An innovative geophysical approach to 2D and 3D RQD estimation is presented in this study. It provides easier, faster, and cheaper access to geomechanical volumetric data. So far, no other work has used non-invasive CSAMT to estimate RQD over 1 km depth in a highly diverse rock setting. The suggested approach provides a more precise and thorough evaluation of the rock’s integrity for the effective installation of the neutrino detector 700 m below ground. The results are significant because they help us make sense of complicated geological situations, estimate the likelihood of early collapse, and build deep underground structures safely, steadily, and affordably. Our approach leads to more objective indices, helps in the development of more accurate geotechnical structures, and reduces inconsistencies between appropriate geomechanical models and sparse data.